FAKTOR RISIKO KEJADIAN ISPA PADA BALITA DI KELURAHAN GADINGREJO KOTA PASURUAN TAHUN 2016 - Zenita .; Nur Haidah; Sukiran Al Jauhari (Poltekkes Kemenkes Surabaya, 2016)
The proportion of under-five deaths due to pneumonia, according Riskesdas 2007 ranks the second after diarrhea. It is estimated that over 2 million children under five die every year from pneumonia. This study aims to identify risk factors of personal hygiene and home cleaning action with URI incident in children under five in Gadingrejo village, Pasuruan. This study uses a case control design. The subject of this study were housewives who have children suffering from URI in December 2015 - January 2016. The sample were 40 cases and 40 controls. Sampling was carriedout by Simple Random Sampling. The data collection technique used questionnaire. The collected data was then analyzed by Odd Ratio calculation. The OR value of personal hygiene with URI was 2.51 and OR value of cleaning action with URI was 2.57. Poor personal hygiene indicated 2.51 times greater risk of a toddler suffering from URI than good personal hygiene. Poor cleaning action also indicated 2.57 times greater risk of a toddler suffering from URI than good house cleaning action. This study indicates that personal hygiene and home cleaning action is a risk factor of URI in children under five in Gadingrejo village, Pasuruan 2016. Counseling regarding hand washing and house cleaning on a regular basis can increase public knowledge that leads to changes in people's behavior. Keywords : Personal Hygiene, House Cleaning Action, URI